The Esteem Need of Margaret Tate’s on The Proposal Movie - Sunarsih Sunarsih; Aulia Putri; Suswanto Ismadi Megah (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2017)
This objective of the study was to describe The Esteem Need . How does healthy self esteem manifest in Margaret Tate’s life viewed from term the psychology self esteem theory. The data analyzed by using the kind of qualitative research. This study tells about Margaret Tate is the professionally well-respected but personally loathed senior editor at a prestigious New York publishing house. Margaret learns that she is being deported back to Canada on expiration of her work visa. To avoid that deportation she and Andrew are engaged and about to get married. In private with Margaret, Andrew agrees to her proposal on the guarantee that he immediately gets promoted to editor and that his own manuscript. From the result of the research showed that Psychological needs have been part of the human needs for life, especially Self-Esteem Needs. It is a powerful of human need and It is life process; the feeling of being worthy, deserving; Experience that we  are appropriate to life and to the requirements of life. Keywords :psychology, self-esteem, life proccess, awarness